A Case of Persistent Retroperitoneal Abscess with Large Right Perinephric Collection - Hashim, Mohd Azren; Kamarulzaman, Mohd Nazli; Md Ralib, Ahmad Razali (IIUM Medical Journal Malaysia, 2020)
Introduction: Retroperitoneal abscess is a rare condition which is difficult to diagnose and treat because of its insidious onset and nonspecific clinical manifestations. Case Report: 55 years old male, underlying DM, Hypertension, Gouty arthritis. Referred to us for right Hypochondriac pain with persistent fever for past 2 days duration. Abdominal examination showed soft, tender over right side of abdomen, localized guarding. An abdominal CT scan showed right pyonephrosis complicated by a large right perirenal collection.Right Nephrostomy was performed. 1 week later, patient had fever and persistent right sided abdominal pain with increasing septic parameters. CT abdomen performed and showed Right pyonephrosis complicated by a large right perinephric abscess extending into the pelvic and inguinal region. Right Perinephric drainage performed. Patient developed worsening sepsis, repeated CT abdomen revealed residual multiloculated right perinephric collection. Open retroperitoneal drainage was performed, noted retroperitoneal abscsess, caccon right kidney and peritoneal, slough ,unhealthy tissue and necrotic debris over right psoas muscles.1 week after surgery, patient still not improving, repeated CT Abdomen showed features of D2 ischemia with focal retroperitoneal perforation causing large and recurrent right perinephric inflammation with increasing intraabdominal free fluid and enlarging right perinephric collection. Laparotomy done shiwed 1L clear ascites intraperitoneally, no pus collection seen. Cocoon inflammatory mass involving hepatic flexure and duodenum to the retroperitoneum, hepatic flexure appeared normal with no intraluminal mass.Right retroperitoneal exploration done, noted adhesion between hepatic flexure to Gerota’s fascia, pus 30ml at upper part of Gerota’s fascia. Repeated CT abdomen showed slightly larger right paracolic gutter collection with similar right perinephric collection. Discussion: Retroperitoneal abscess is very rare. Retroperitoneal abscess may result from a variety of causes, such as pyelonephritis, pancreatitis, retroperitoneal appendicitis, diverticulitis, peptic ulcer disease, perforated cancer, infammatory bowel disease, spinal infection, trauma, and post instrumentation. For our patient ,the exact aetiology of retroperitoneal collection and peri renal collection are still unknown.